2011
DOI: 10.1091/mbc.e11-01-0047
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of estradiol 17β-d-glucuronide–induced canalicular transporter internalization by hormonal modulation of cAMP in rat hepatocytes

Abstract: Glucagon- and salbutamol-derived cAMP prevents estrogen-induced alteration of canalicular transporter localization and function via different pathways. Glucagon-derived protection depends on PKA activation, whereas salbutamol protection is exerted through a pathway that depends on Epac/MEK and microtubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 48 publications
7
34
0
Order By: Relevance
“…The likely involvement of PKA in E17G‐induced secretory failure was evaluated by incubating IRHCs with the PKA inhibitors, KT5720 (KT; 250 nM), H89 (1μM), or Rp‐cAMPS (Rp; 10 μM), for 15 minutes. Activation of PKA was confirmed evaluating phospho‐PKA substrates by western blotting …”
Section: Methodsmentioning
confidence: 99%
“…The likely involvement of PKA in E17G‐induced secretory failure was evaluated by incubating IRHCs with the PKA inhibitors, KT5720 (KT; 250 nM), H89 (1μM), or Rp‐cAMPS (Rp; 10 μM), for 15 minutes. Activation of PKA was confirmed evaluating phospho‐PKA substrates by western blotting …”
Section: Methodsmentioning
confidence: 99%
“…While the protective effect of glucagon is dependent on PKA, but not EPAC, salbutamol's effect is EPAC/MEK dependent and PKA independent. Mechanistically, salbutamol/EPAC promotes a microtubule-dependent and long-range trafficking of Abcb11/Abcc2-containing vesicles, whereas glucagon/ PKA modulates the microfilament-mediated fusion of these vesicles with the apical membrane (1217). In a follow-up study, the preventive effects of salbutamol and glucagon were further validated in more physiological settings using perfused rat liver and in vivo alanine administration, which induces pancreatic glucagon secretion (1218).…”
Section: Epac Proteins and Hepatic Functionsmentioning
confidence: 96%
“…Data are expressed as mean ± standard error of the mean (SEM; n = 5) ▸ Hayashi et al (2012) demonstrated that internalization of Abcb11, a canalicular bile salt transporter, is clathrinmediated. Though the information about the mechanism of Abcc2 internalization is lacking, a similar mechanism is possible since confocal images in previous works showed that E17G action produced similar pattern of endocytosis of Abcb11 and Abcc2 Boaglio et al 2010;Crocenzi et al 2008;Zucchetti et al 2011).…”
Section: Discussionmentioning
confidence: 92%
“…These proteins are organized in several signaling pathways. Up to now there are evidences that support a pathway that involves ERα, PKC, and p38-MAPK responsible for the initial endocytic internalization of canalicular transporters, and pathways initiated in the action of E17G on its receptor GPR30 that activate either adenylyl cyclase-PKA or PI3K-Akt-ERK1/2, being the latter pathway responsible for keeping transporters in a subapical space, restraining reinsertion Boaglio et al 2010Boaglio et al , 2012Crocenzi et al 2008;Zucchetti et al 2011Zucchetti et al , 2014.…”
Section: Introductionmentioning
confidence: 99%